Patriotisme Kristen: Pembelajaran PAK Keluarga Pada Anak Usia Dini - Sozanolo Telaumbanua; Desi Sianipar (Jurnal Shanan, 2021)
The formation of patriotism in early childhood is very important because this will seriously impact on the welfare, prosperity and progress of family, society, and the nation in the future. In particular, this is a concern for Christian parents in responding to social situations at present, which are marked by the development of unpatriotic attitudes and actions, such as corruption, acts of violence, bullying, hate speech, intolerance, terrorism, efforts to disrupt the unity of the state, abuse of technology, laziness, individualism, lack of respect for the culture and production of his/her own country, and so on. The Indonesian government is also preparing the strong generation to welcome the demographic bonus between 2010-2035. In supporting the government, Christian parents must realize their role in educating their children to have patriotism from an early age. Therefore, this study aims to describe how Christian patriotism is taught to early childhood through Christian religious education in family. The method used is a qualitative research method with the literature review approach. The result of this research is that parents build early childhood patriotism based on Christian values, namely by having an understanding of the theological foundation of patriotism; early childhood development, and the formation of patriotism by setting learning objectives, learning materials and learning methods adapted to early childhood development and Christian values.